Crisis in Venezuela, or the Bolivarian Dilemma: To Revolutionize or to Perish? A Kaleckian Interpretation - Lampa, Roberto (2017)
This paper investigates the evolution of Venezuela’s political and economic scenario over the last 15 years. I explore in depth both the achievements and the unsolved problems of the Venezuelan demand-led growth model. Recalling Kalecki’s analysis of underdevelopment, I highlight Venezuela’s problems that depend on the constraining role played by the existing institutions. I conclude that the real challenge consists of a deep institutional change, possibly along the lines portrayed in the 2007 constitutional referendum.